Spillover effects from inter-governmental transfers between local jurisdictions in Brazil - MELO, LB (2023)
This paper estimates fiscal spillover effects between local jurisdiction in Brazil. The central government transfers revenues to local jurisdictions. By using an Event Study design, it shows evidences that arguable exogenous changes in revenues of a local jurisdiction has null causal spillover effects on public expenditures and number of firms of a nearby jurisdiction. When restricting the sample for jurisdictions that receive the revenue shock that are larger than their nearby jurisdictions, the result of null fiscal spillover still holds. This novel results cast doubts on a rich theoretical literature that predicts fiscal spillover's existence and also on the current empirical literature that estimates positive fiscal spillovers. JEL: H27,H30,H50,H61